Existence of C1-Positive Solutions for a Class of Second-Order Impulsive Differential Equations - Hong Li (Complexity)
In this study, under some inequality conditions, necessary and sufficient conditions, using fixed-point theorem in cones, are established for the existence of C1-positive solutions for a class of second-order impulsive differential equations. Two examples are given in the last section to illustrate the abstract results.